PERANCANGAN DAN PELATIHAN PENGGUNAAN ALAT PEMOTONG KERUPUK UNTUK MENINGKATKAN EFEKTIVITAS PRODUKSI PADA UMKM KERUPUK DI SIDOARJO - Yuliawati, Evi; Andrianto Pratama Sugiarto, Vito; Widad Saputri, Aisyatul; Maulana Ishaq, Ardan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the local economy, but many still face obstacles in production efficiency due to technological limitations. Pak Mualiman's Onion Cracker MSME in Sidoarjo Regency is one of the MSMEs that still cuts cracker dough manually, which is time-consuming, produces uneven thickness, and causes worker fatigue. This community service activity aimed to design and provide training on the use of a simple, safe cracker cutting tool that is suitable for the operational conditions of the partner MSME. The implementation method included identifying needs, designing the tool, providing training on its use, and evaluating the application of the tool in the production process. The results of the activity show that the use of the cutting tool can reduce cutting time from 180 minutes to 60 minutes, improve the consistency of the thickness of the pieces to 3 mm, and improve the working position of the operator. These findings indicate that the application of appropriate technology can significantly improve the efficiency and productivity of MSMEs and support business sustainability.